Oxidative stress and inflammation on metabolic abnormalities and renal involvement in prediabetic subjects across Europe. - Mas-Fontao, Sebastián; Civantos, Esther; Boukichou-Abdelkader, Nisa; Soto-Catalan, Manuel; Romeo-Colas, Marta; Marco, Arantxa; Gomez-Guerrero, Carmen; Moreno, Juan Antonio; Tuomilehto, Jaakko; Gabriel, Rafael; Egido, Jesús (Nefrología, 2025)
Background: Studying the mechanisms Involved in the transition from prediabetes to diabetes and its associated complications, such as kidney disease, is a growing challenge. This study focuses on identifying valuable biomarkers for the early detection of kidney damage, evaluating molecules associated with oxidative stress and inflammation in prediabetic individuals across Europe. Methods:In plasma samples from individuals with prediabetes included in the ePREDICE study, we determined molecules related to oxidative stress (advance oxidative protein products-AOPP) and inflammatory biomarkers (C-reactive protein - CRP; Interleukin 6 - IL-6), and correlated them with anthropometric and biochemical data, assessing their potential for the early diagnosis of renal involvement. Results:Among the 967 people with prediabetes, 94 presented some sign of renal impairment such as albuminuria, hyperfiltration or hypofiltration. Significant variations were identified between oxidative stress and inflammatory biomarkers (upper and lower quartiles of AOPP, CRP and IL6), and parameters associated with blood pressure, glucose metabolism, lipid profile, and fatty liver index. In particular, both types of biomarkers were associated with components of the metabolic syndrome. There were significant associations between AOPP and CRP, and the presence of albuminuria, but not with renal function. Overall, CRP was a better biomarker than IL-6 for most of the parameters studied. Conclusion:These results highlight the important associations of oxidative stress and inflammation with metabolic abnormalities linked to the prediabetic state and its complications such as fatty liver and renal involvement. Although these results need to be confirmed, our study suggests that AOPP and CRP could be simple biomarkers of interest in predicting the risk of loss of renal function in people with prediabetes.